The Effects of Using a Ramp and Elevator to Load and Unload Trailers on the Behavior and Physiology of Piglets - John McGlone; Avi Sapkota (Animals, 2014)
Transport is an inevitable process in the modern U.S. swine industry. The loading process is a novel and potentially stressful experience. This study uses behavior, heart rate and leukocyte counts to compare stress one hour before, during and after loading via ramp or elevator. Piglets were held in a home pen (control (CON)), walked up and down an aisle (handled (HAN)), or walked to a truck and loaded via elevator (ELE) or ramp (RAM). Sitting, feeding and blood parameters did not show a significant treatment by time effect (p > 0.05). Standing behavior did not differ between CON and HAN piglets nor between RAM and ELE piglets (p > 0.05); however, CON and HAN piglets stood more than RAM and ELE piglets during treatment (p < 0.05). After treatment, drinking behavior was increased in RAM piglets (p < 0.05). The heart rate of ELE piglets decreased 6.3% after treatment; whereas the heart rate of RAM piglets remained elevated 2.4% (p < 0.05). In terms of heart rate, loading by elevator appears to be less stressful than loading by ramp.